Waris Beda Agama dalam Kitab Bidayatul Mujtahid - Ma'mun, Mohamad (MAHAKIM Journal of Islamic Family Law, 2024)
In Islamic inheritance law, it has been explained in detail and clearly about the procedures for the distribution and transfer of inheritance to the heirs and the things that prevent the heirs from getting the inheritance from the heir. This prohibition is based on the hadith of the prophet. However, this law is not a single law, there are differences of opinion among scholars. This type of research is qualitative research, which in the study process used library material (library research) which examines library material related to Ibn Rushd's legal istinbath method in the Book of Bidayatul Mujtahid wa Nihayatul Muqtasid about the inheritance of different religions. From the results of the author's research, there are several results, namely: Ibn Rushd in deciding an Islamic law employment the Qur'an and al-Sunnah as the most premise. But since the two sources are exceptionally constrained, he too employments ijtihad as an elective strategy to unravel the developing issues of Sharia law. In fathoming the progressively complex issues of Sharia law, Ibn Rushd broadly utilized qiyas (similarity). Another result regarding inheritance from different religions, in the Bidayatul Mujtahid book, is explained: First, there is no inheritance between the two. Regarding inheritance between different religions, the book Bidayatul Mujtahid explains: First, there is no inheritance between the two. Given the concept of fiqh mawaris, a Muslim cannot inherit the property of a non-Muslim, and vice versa a non-Muslim cannot inherit the property of a Muslim. Secondly, Ats-Tsauri and the majority of the scholars of Kuffah, as well as the majority of the scholars of Basrah think that his inheritance can be passed on to Muslim heirs, but not vice versa. This opinion was also derived from Ibn Mas'ud and Ali ibn Abi Talib.